2021
DOI: 10.1111/acer.14693
|View full text |Cite
|
Sign up to set email alerts
|

Forgoing plans for alcohol and cannabis use in daily life: Examining reasons for nonuse when use was planned in a predominantly white college student sample

Abstract: BackgroundThe reasons for college students to abstain from alcohol and cannabis use on a given day can inform efforts to prevent or intervene in those behaviors. Research on reasons for alcohol nonuse remains in its nascent stages and no study to date has examined reasons for cannabis nonuse on a given day. Here we examine reasons for nonuse among college students after they planned to use alcohol and/or cannabis.MethodsCollege students (N = 341; Mage = 19.79; 53% women; 74% White) from 3 universities complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…A recent study by Stevens et al (2021) (33) pointed out that although there are many studies focused on the motivations related to why individuals drink, studies on reasons for not drinking at all or on a given day are less frequent, and found that the variability in non-use of alcohol on day when use was planned occurred more frequently at the within-person level (26%) than at the between-person level (74%) and recommended future studies could bene t from offering a free response option. This kind of study could make a signi cant contribution to enhancing alcohol or other drugs-related preventive or harm reduction interventions.…”
Section: Introductionmentioning
confidence: 96%
“…A recent study by Stevens et al (2021) (33) pointed out that although there are many studies focused on the motivations related to why individuals drink, studies on reasons for not drinking at all or on a given day are less frequent, and found that the variability in non-use of alcohol on day when use was planned occurred more frequently at the within-person level (26%) than at the between-person level (74%) and recommended future studies could bene t from offering a free response option. This kind of study could make a signi cant contribution to enhancing alcohol or other drugs-related preventive or harm reduction interventions.…”
Section: Introductionmentioning
confidence: 96%
“…A recent study by Stevens et al (2021) [ 33 ] pointed out that although there are many studies focused on the motivations related to why individuals drink, studies on reasons for not drinking at all or on a given day are less frequent. They reported that the variability in non-use of alcohol on days when the use was planned occurred more frequently at the within-person level (26%) than at the between-person level (74%).…”
Section: Introductionmentioning
confidence: 99%